2014
DOI: 10.1128/iai.01795-14
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid CDS5 Influences Infectivity and Virulence in a Mouse Model of Chlamydia trachomatis Urogenital Infection

Abstract: eThe native plasmid of both Chlamydia muridarum and Chlamydia trachomatis has been shown to control virulence and infectivity in mice and in lower primates. We recently described the development of a plasmid-based genetic transformation protocol for Chlamydia trachomatis that for the first time provides a platform for the molecular dissection of the function of the chlamydial plasmid and its individual genes or coding sequences (CDS). In the present study, we transformed a plasmid-free lymphogranuloma venereum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 40 publications
0
40
0
Order By: Relevance
“…Third, Pgp3 forms a stable trimer (45) with a C-terminal trimerization domain similar to the receptor binding domain of tumor necrosis factor alpha (TNF-␣) (46), which suggests that Pgp3 is poised to interact with host inflammatory responses. Finally, Pgp3-deficient C. trachomatis serovar L2 is attenuated in infecting the mouse genital tract and inducing inflammatory responses (29).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, Pgp3 forms a stable trimer (45) with a C-terminal trimerization domain similar to the receptor binding domain of tumor necrosis factor alpha (TNF-␣) (46), which suggests that Pgp3 is poised to interact with host inflammatory responses. Finally, Pgp3-deficient C. trachomatis serovar L2 is attenuated in infecting the mouse genital tract and inducing inflammatory responses (29).…”
Section: Figmentioning
confidence: 99%
“…In contrast, deficiencies in Pgp3, -5, or -7 did not significantly affect the expression of other chlamydial genes. Ramsey et al (29) recently evaluated an L2 organism with a pgp3 gene deletion in the mouse model and found that the Pgp3 deficiency significantly attenuated L2 infectivity and pathogenicity in the mouse genital tract. However, because of the failure of the wild-type L2 organisms to induce hydrosalpinx in mice, it remains unclear whether Pgp3 or any other plasmid-encoded factors are required for chlamydial induction of the longlasting hydrosalpinx (11,30) that is most relevant to C. trachomatis-induced tubal factor infertility in women (31).…”
mentioning
confidence: 99%
“…It remains unknown how C. trachomatis establishes a successful initial infection in the lower genital tract and achieves ascending infection. The mouse genital tract infection model has been used with either C. trachomatis (3)(4)(5)(6)(7) or C. muridarum (8)(9)(10)(11)(12)(13)(14)(15) for studying chlamydial pathogenesis and immunity. C. trachomatis infection in the mouse genital tract, unlike C. muridarum infection, often fails to induce a long-lasting upper genital tract pathology such as hydrosalpinx.…”
mentioning
confidence: 99%
“…The recent success in transforming Chlamydia (26,(31)(32)(33)36) should facilitate the identification of the plasmid-dependent virulence factors. Indeed, the plasmid-encoded Pgp3, an immunodominant (37), trimeric (38,39), and secretion (14) protein, has been shown to play a significant role in C. trachomatis L2 infection of the mouse genital tract (40) and C. muridarum induction of hydrosalpinx (41).…”
Section: Discussionmentioning
confidence: 99%